Асинхронний вентильний генератор в якості керованого джерела струму - Мазуренко, Леонід Іванович; Романенко, Володимир Іванович (НТУ "ХПІ", 2010)
In this paper an isolated induction generator with inverter excitation for arc welding supply is presented. Inverter is acting like VAR compensator and welding current controller. The stable operation in all working region is obtained due to using a variable structure programmable control system. To avoid a loss of excitation a variable resistance is connected in series with the main load (welding arc) at the DC-side circuit. Experimental results show that proposed generator is suitable for arc welding supply.
An inverter excited induction generator as a control current source
Keywords: конденсатор; зварювання; двигун привідний; обмотка статора; вентильна система збудження; блок датчиків; система керування; опір регульований; датчик напруги